Age Standardization of Epidemiological Frequency Measures: Part 37 of a Series on the Evaluation of Scientific Publications. - Stang, A.; Gianicolo, E. (Deutsches Ärzteblatt International, 2025)
Background: When raw incidence rates are compared across populations, age can be a major confounding factor if the populations differ in age structure. In this paper, we elucidate the principles of age standardization of rates. Methods: Crude and age-standardized rates are derived, and methodological aspects explained, in the light of pertinent publications from a selective literature search and by means of a particular example: a comparison of the incidence of stomach cancer in Cali, Colombia, and in the German federal state of North Rhine-Westphalia (NRW) (2013-2017, men). Results: The crude incidence rates were 21.5 per 100 000 person-years in Cali and 22.9 per 100 000 person-years in NRW, but the corresponding age-standardized incidence rates (old European standard) were 30.0 and 15.7 per 100 000 person-years, respectively. Because of the markedly different age structures of the two populations, the crude incidence misleadingly suggested a practically identical incidence of stomach cancer in Cali and in North Rhine-Westphalia. Age standardization revealed a markedly higher incidence in Cali. Conclusion: The numerical value of a standardized rate is an artificial rate that can only be interpreted in the light of the standard used. Standardization only makes sense if rates are to be compared across populations, where a difference in a particular factor (e.g., age) might distort the comparison. Standardization is not needed to describe the epidemiological situation in a single population.